Operation and Maintenance of Thermal Power Stations Best Practices and Health Monitoring - Chanda, Pradip; Mukhopaddhyay, Suparna (Energy Systems in Electrical Engineering,, 2016)
This book illustrates operation and maintenance practices/guidelines for economic generation and managing health of a thermal power generator beyond its regulatory life. The book provides knowledge for professionals managing power station operations, through its unique approach to chemical analysis of water, steam, oil etc. to identify malfunctioning/defects in equipment/systems much before the physical manifestation of the problem. The book also contains a detailed procedure for conducting performance evaluation tests on different equipment, and for analyzing test results for predicting maintenance requirements, which has lent a new dimension to power systems operation and maintenance practices. A number of real life case studies also enrich the book. This book will prove particularly useful to power systems operations professionals in the developing economies, and also to researchers and students involved in studying power systems operations and control. .